Formulation of topical dosage form of Pangasius sutchi and their wound healing activities - Omar, Muhammad Nor; Hajazi, Nurhani Fadzil; Zuberdi, Ahmad Muzammil; Ahmad, Kausar (2011)
Fish oil is associated with many promising health benefit since it contains an essential fatty acid called ω fatty acid (1, 2). This experiment was conducted to study the effect of fish oil containing ω -3 fatty acids on wound healing. A freshwater fish, Pangasius sutchi was used to extract its oil using a modified Folch method (3). The fatty acid profile of the fish oil was determined using a GC/MS instrument (2,4). A topical cream containing the fish oil extract was formulated and stability test including particle size analysis were carried out. The formulated cream was tested on Sprague Dawley rats for wound healing properties. A hole was punctured at the back of the rat’s neck using biopsy punch and cream was applied twice daily. The diameter of the wound was recorded every two days. It was found that the topical cream containing P. sutchi oil exhibited wound healing properties, however, the time taken for the rat’s wound to heal was not significantly different from the control groups.